Obstructive sleep apnea during rapid eye movement sleep: clinical relevance and therapeutic implications. Issue 6 (November 2016) - Alzoubaidi, Mohammed; Mokhlesi, Babak
Abstract : Purpose of review: Obstructive sleep apnea (OSA) is a highly prevalent condition that has been associated with cardiovascular morbidity and mortality, impaired glucose metabolism and daytime functional impairment. Compared with nonrapid eye movement sleep, rapid eye movement (REM) sleep is associated with higher sympathetic activity and cardiovascular instability in healthy individuals and more so in patients with OSA. Recent findings: Recent studies have indicated that REM OSA is independently associated with prevalent and incident hypertension, nondipping of nocturnal blood pressure, increased insulin resistance and impairment of human spatial navigational memory. Summary: These findings have significant clinical implications for the duration of continuous positive airway pressure (CPAP) use that is needed to decrease the health risks associated with OSA. Further research is needed to establish the duration of CPAP needed to effectively treat REM OSA and to evaluate patients with REM OSA with an overall normal apnea-hypopnea index.